Achieving low-power single-wavelength-pair nanoscopy with NIR-II continuous-wave laser for multi-chromatic probes - Xin Guo; Rui Pu; Zhimin Zhu; Shuqian Qiao; Yusen Liang; Bingru Huang; Haichun Liu; Lucía Labrador-Páez; Uliana Kostiv; Pu Zhao; Qiusheng Wu; Jerker Widengren; et al. (Nature Communications, 2022)
The authors introduce stimulated-emission induced excitation depletion (STExD) nanoscopy using a single pair of low-power, near-infrared, continue-wave lasers. Emission of multichromatic probes is inhibited by cascade amplified depletion in lanthanide upconversion systems induced by manipulating their common sensitizer.